Diseño y construcción de un equipo de Galvanotecnia basado en instrumentación virtual utilizando la técnica de corriente directa de deposición. - Araque Idrovo, Marvin Xavier (2010)
The present Thesis Project has the purpose to “DESIGN AND BUILD A GALVANOTECHNIA EQUIPMENT USING THE DIRECT FLUID OF DEPOSITION TECHNIQUE”, which allows us to contribute in the theoretical and practical students training of the Energy, Industries and Non-Renewable Resources Area of National University of Loja. The presented machine in this project has three basic components: mechanical or structural part, the electrical one and virtual implementation. In this thesis the LabVIEW software is used as tool for acquisition of voltage, intensity and temperature values of the solutions during the electrodepositing process, and it also controls the heating utensils which maintain the solutions of nickel and hard chromium to a suitable temperature to work.